KOMPETENSI DI DUNIA REALITAS SETELAH LULUS SMA - Putlia, Grace; Sundoro, Hary S; Alvita, Meilisa; Wijaya, Brendi; Wardhana, Ali; Rowena, Janny; Wilson, Nicholas; Budi, Budi; Samuel, Samuel (Jurnal Pengabdian dan Kewirausahaan, 2020)
Considering that teenagers in the future will be the next generation, the future must be approved. Tri Dharma of higher education related to Pengabdian Kepada Masyarakat (PKM), which refers to the responsibilities of teachers including transferring, transforming, and using knowledge from within the campus for the community. Based on this, Bunda Mulia University conducted PKM activities by raising the topic " Kompetensi di Dunia Realitas setelah Lulus SMA". The participation of the study participants was adjusted to the topic Tunas Indonesia School students. The method used in this PKM is an ice breaking session, sharing of material, role playing as a practical tool for participants as well as question and answer sessions so that two-way communication can be used. In summary, life goals, self-development, the importance of soft skills in achieving our goals, and success in the world of work. Each session is twenty minutes long. In the future, the activity of PKM is expected to be held again, of course with more diverse topics and bring benefits. Keywords: competence, graduated high school, PKM, life goals.